Effect Of Different Yeast Extract Concentration In Membrane-less Microbial Fuel Cell (Ml-mfc) For Electricity Generation Using Food Waste As Substrate - Mirza Mohammad Faizal, Mohammad (Pusat Pengajian Teknologi Industri, 2020)
Electricity is the basic energy in our daily life and there are about 14 % of global population that did not get the access to electricity. Furthermore, 45 % of the main composition of waste that produced daily is food waste. As a result, microbial fuel cell (MFC) become the solution as it has the potential for food waste treatment and electricity power generation. This study is being conducted to utilize the food waste that collected from E-Idaman, Kedah, to generate energy while focusing the effect of different yeast extract level in a membrane-less microbial fuel cell (ML-MFC). The electrogenic bacterial culture that acted as a catalyst for electricity power generation was isolated from previous working ML-MFC. The proximate analysis of food waste revealed that carbon has the highest composition with 30.02 %. From the preliminary study that compared three different strains of electrogenic bacteria to introduced in the ML-MFC, Bacillus subtillis sp. showed the highest specific growth rate, µ, (0.117 gL-1/h) and doubling time, Td, (5.93 h). The performance of the ML-MFC was evaluated using one-factor-at-a-time (OFAT) method. The highest voltage generation (820 mV) and power density (9576.14 mW/m2) were obtained in 5 g/L yeast extract concentration ML-MFC. The highest substrate degradation efficiency (12.3 %), COD removal (99 mg/L) and biomass (44.32 mg/L) were in 15 g/L yeast extract concentration ML-MFC. It showed that the yeast extract concentration and food waste affect the performance of ML-MFC.